2011
DOI: 10.1111/j.1365-3121.2011.01006.x
|View full text |Cite
|
Sign up to set email alerts
|

Emplacement and exhumation of the Kuznetsk‐Alatau basement (Siberia): implications for the tectonic evolution of the Central Asian Orogenic Belt and sediment supply to the Kuznetsk, Minusa and West Siberian Basins

Abstract: New geochronological data [zircon U/Pb, titanite fission-track (TFT) and apatite fission-track (AFT) dating and apatite (U-Th-Sm)/He thermochronology] and thermal history modelling yield constraints on the development of the granitoid basement of the Kuznetsk-Alatau Mountains, southern Siberia. The final stages of magmatism in the Kuznetsk-Alatau palaeo-island-arc are Late Cambrian, and collision of the arc with Siberia occurred in the Early Ordovician. The basement was exhumed by the Early Devonian. Continuou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(10 citation statements)
references
References 41 publications
1
9
0
Order By: Relevance
“…Late Jurassic-Early Cretaceous exhumation in the Tian Shan was also interpreted as an effect of the Lhasa-Qiangtang collision (Dumitru et al, 2001;De Grave et al, 2007;Glorie et al, 2010;De Grave et al, 2012). Therefore, although the Late Jurassic-Early Cretaceous cooling episode in the northern Altai Shan (De Grave and Van den haute, 2002;De Grave et al, 2008), Sayan ranges (De Grave et al, 2011;Jolivet et al, 2013), and neighboring areas of Lake Baikal ( Van der Beek et al, 1996;Jolivet et al, 2009) have been ascribed to the Mongol-Okhotsk orogeny, to what extent the Late Jurassic-Early Cretaceous large scale reactivation in the western CAOB was related to this collisional event has remained unclear De Grave et al, 2011).…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Late Jurassic-Early Cretaceous exhumation in the Tian Shan was also interpreted as an effect of the Lhasa-Qiangtang collision (Dumitru et al, 2001;De Grave et al, 2007;Glorie et al, 2010;De Grave et al, 2012). Therefore, although the Late Jurassic-Early Cretaceous cooling episode in the northern Altai Shan (De Grave and Van den haute, 2002;De Grave et al, 2008), Sayan ranges (De Grave et al, 2011;Jolivet et al, 2013), and neighboring areas of Lake Baikal ( Van der Beek et al, 1996;Jolivet et al, 2009) have been ascribed to the Mongol-Okhotsk orogeny, to what extent the Late Jurassic-Early Cretaceous large scale reactivation in the western CAOB was related to this collisional event has remained unclear De Grave et al, 2011).…”
Section: Introductionmentioning
confidence: 92%
“…11B). Fission-track analyses have shown that many places, including neighboring areas of Lake Baikal ( Van der Beek et al, 1996;Jolivet et al, 2009), Sayan ranges (De Grave et al, 2011;Jolivet et al, 2013), Altai ranges (De Grave and Van den haute, 2002; Guo et al, 2006;De Grave et al, 2008), North Tian Shan (NTS) (Guo et al, 2006;Shen et al, 2008), and South Tian Shan (STS) (Dumitru et al, 2001;Jolivet et al, 2010), underwent a cooling event in the latest Jurassic-earliest Cretaceous (Figs. 1, 11B).…”
Section: The Short-lived Mongol-okhotsk Collisional Orogeny During Thmentioning
confidence: 99%
“…The Early Jurassic and Late Jurassic exhumation events in the Tian Shan have also been interpreted as effects of the Asia‐Qiangtang collision and Asia‐Lhasa collision, respectively [ Dumitru et al ., ; De Grave et al ., , , ; Glorie et al ., ; Zhang et al ., ]. However, Jurassic‐Early Cretaceous exhumation events in the Altai Shan [ De Grave and Van den haute , ; Vassallo et al ., ; De Grave et al ., , ], Sayan ranges [ De Grave et al ., ; Jolivet et al ., ], and neighboring areas of Lake Baikal [ Van der Beek et al ., ; Jolivet et al ., ] have been commonly attributed to far‐field effects of the closure of the Mongol‐Okhotsk Ocean in the Mesozoic [ Zonenshain et al ., ; Zorin , ]. Because accretion of Tibet and the Amuria‐Siberia collision occurred, respectively, to the south and to the east of the Junggar Basin (Figure ), they might have produced different effects on structural deformation and stratigraphic architecture within the basin.…”
Section: Introductionmentioning
confidence: 99%
“…The uppermost sediments of the basin are mudstones, siltstones, and sandstones that contain only sparse and thin coal layers, and which belong to the Middle–Upper Permian Kolchugin Group (Kotel'nikov et al, ). In terms of composition and texture, the deposits of the Balakhon and Kolchugin groups in the Gorlovo Basin are similar to the same stratigraphic units in the Kuznetsk Basin (Davies, Allen, Buslov, & Safonova, ; De Grave et al, , and references therein). This Serpukhovian–Permian unit has a thickness of about 2,500 m, 1,150 m of which is represented by the Upper Carboniferous–Lower Permian Balakhon Group.…”
Section: Geological Settingmentioning
confidence: 68%